Health informatics : an interprofessional approach - Nelson, Ramona; Staggers, Nancy co-author (St. Louis, Missouri : Elsevier, 2018)
See how information technology intersects with health care! Health Informatics: An Interprofessional Approach, 2nd Edition prepares you for success in today's technology-filled healthcare practice. Concise coverage includes information systems and applications such as electronic health records, clinical decision support, telehealth, ePatients, and social media tools, as well as system implementation. New to this edition are topics including data science and analytics, mHealth, principles of project management, and contract negotiations. Written by expert informatics educators Ramona Nelson and Nancy Staggers, this edition enhances the book that won a 2013 American Journal of Nursing Book of the Year award!
Unit 1: Foundational Information in Health Informatics 1. Health Informatics: Introduction, Definition and Significance 2. Theoretical Foundations of Health Informatics 3. Use of Evidence Based Practice and Practice Based Evidence in Health Informatics 4. Models, Theories and Research for Program Evaluation 5. Technical Infrastructure to Support Healthcare Unit 2: Information Systems and Applications For the Delivery of Health Care6. Electronic Health Records and Applications for Managing Patient Care 7. Administrative Application in Healthcare8. Telehealth and Applications for Delivering Care at a Distance9. Home Health and Related Community Based Systems 10. Clinical Decision Support Systems in Healthcare 11. Public Health Informatics Unit 3: Participatory Health Care Informatics12. The Engaged ePatient 13. Social Media Tools for Practice and Education 14. Personal Health Records 15. mHealth - The Intersection of Mobile Technology and Health NEW!Unit 4: Managing the Life Cycle of a Health Information System16. Strategic Planning and Selecting an Information System 17. Project Management Principles for Health Informatics NEW!18. Contract Negotiations and Software Licensing NEW!19. Implementing and Upgrading an Information System20. Downtime and Disaster Recovery for Health Information Systems Unit 5: Usability, Standards, Safety and Analytics in Health Informatics 21. Improving the User Experience for Health Information Technology22. Informatics Related Standards and Standards and Standard Setting Organizations 23. Data Science and Analytics in Healthcare NEW!24. Patient Safety and Quality Initiatives in Health Informatics Unit 6: Governance Structures, Legal, and Regulatory Issues in Health Informatics25. Legal Issues, Federal Regulations, and Accreditation NEW!26. Privacy and Security 27. The Health Information Technology for Education and Clinical Health (HITECH) Act, Meaningful Use (MU) and Medicare Access & CHIP Reauthorization Act of 2015 (MACRA) NEW!28. Health Policy and Informatics 29. Health Information Technology GovernanceUnit 7: Education and Health Informatics30. Informatics in the Curriculum for Healthcare Professionals 31. Distributive Education: Applications, Techniques and Issues 32. Informatics Tools for Educating Health Professionals33. Simulation in Healthcare Education Unit 8: International Health Informatics Efforts34. International Efforts, Issues and Innovations Unit 9: Exploring the Past and the Future35. The Evolving History of Health Informatics36. Future Directions and Future Research in Health Informatics
Includes bibliographical references and index.
Keywords: MEDICAL INFORMATICS